Multiple Choice Questions Revisited: Improvement of Validity for Fair Tests - Abdalla, Mohamed Elhassan (مجلة الجزيرة للعلوم الصحية; مجلد 9 عدد 1 (2013), 2013)
In the last two decades there is a vast increase in the number of medical schools all over the world, especially in the Eastern Mediterranean Region (EMRO). This necessitates the existence of faculty development programme for the increasing staff. The objective of this communication is to revisit the multiple choice question elaborate on factors that will affect its validity, aiming at having acceptable fair test for the students. This communication describe the major threats of validity of multiple choice questions , namely the construct under representation (CU) and the construct irrelevant (CIV) threats and it describe how can they be overcome. The communication concluded that faculty development programmes and the use of guidelines and blueprint will lead to improvement in the tests validity in medical schools.